INFORMATION SUPPORT OF RESEARCH ON TRANSCRIPTIONAL REGULATORY MECHANISMS: AN ONTOLOGICAL APPROACH - N. L. Podkolodnyy; E. V. Ignatieva; O. A. Podkolodnaya; N. A. Kolchanov (Вавиловский журнал генетики и селекции, 2014)
By now, a huge body of experimental data on gene transcription regulation has been accumulated. Transcription is controlled by a great number of proteins acting at various steps of the process; thus, a diversity of regulatory mechanisms can be realized. This paper presents approaches to building knowledge domain ontology, formalized description of the mechanisms of transcriptional regulation and the development of methods for integration of heterogeneous information on the features of the regulation of gene expression on this base. The pilot version of the knowledge base on the transcriptional regulation of eukaryotic genes includes: (1) description of basic terms related to transcription regulation and relationships between them; (2) hierarchical classification of transcription regulators; (3) classification of phases and steps of transcription; (4) a database of transcriptional regulators of three mammalian species (human, mouse, and rat); and (5) dictionaries for molecular processes involved in transcriptional regulation. The knowledge base is designed for information support of computer analysis of transcriptional regulatory mechanisms. Approaches to reconstruction of eukaryotic transcriptional regulatory mechanisms with the new knowledge base are presented.